Living streets strategies for crafting public space - Bain, Lesley 1955-; Gray, Barbara 1966-; Rodgers, Dave 1969- (Hoboken, N.J. Wiley, 2012)
"Written for teams of engineers, transportation planners, landscape architects, and urban planners, this book provides a broad overview of the growing approach towards complete and sustainable street design. Its contents present the background on modern street design and where it has failed, describe a series of street typologies, and demonstrate, through geographically diverse case studies, the applicable lessons learned from each. Featuring examples from over two dozen completed street design projects around the world, it provides practical guidance on the complete street approach to sustainable and community-minded street and road design"--Provided by publisher.
Serves to provide practical guidance on the complete street approach to sustainable and community-minded street and road design. Written for teams of engineers, transportation planners, landscape architects and urban planners, the book provides a broad overview of the design and policy tools that have been successful, presents background on modern street design and where it has failed in many aspects, describes a series of street typologies, and demonstrates, through a variety of geographically diverse case studies, the applicable lessons learned from each
Keywords: City planning; Sustainable urban development; Community development